Intergeneric hybrids of Phalaenopsis 2166 x Vanda ‘Saint Valentine’ showing maternal inheritance: Genetic analysis based on ndhE partial gene - Murni Dwiati; Agus Susanto; Lucky Prayoga (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dwiati M, Susanto AH, Prayoga L. 2020. Intergeneric hybrids of Phalaenopsis 2166 x Vanda ‘Saint Valentine’ showing maternal inheritance: Genetic analysis based on ndhE partial gene. Biodiversitas 21: 5138-5145. Genetic characterization in the intergeneric hybridization of orchids employing a particular molecular marker, such as ndhE gene, is needed to avoid phenotypic plasticity. The hybridization between Phalaenopsis 2166 as a female parent and Vanda ‘Saint Valentine'as a male parent has been successfully made to produce various leaf shapes and colors of the hybrid seedlings, which tend to resemble those of the female parent. This study aims to assess whether the maternally phenotypic traits of the hybrids of Phalaenopsis 2166 x Vanda ‘Saint Valentine’ are congruent with the inheritance pattern of ndhE partial sequences. The result reveals that the ndhE partial sequences of the hybrids are seemingly similar to that of Phalaenopsis 2166 as the female parent rather than to that of Vanda ‘Saint Valentine’. It is also found that three hybrids, i.e. F1.9, F1.11, and F1.14 show slightly different ndhE partial sequences from those of the other hybrids in that some base substitutions are observed. In general, the ndhE partial sequences of the hybrids are maternally inherited. This finding provides a fact that maternally phenotypic traits of the hybrids of Phalaenopsis 2166 x Vanda ‘Saint Valentine’ have strong genetic background rather than environmental involvement.